Phaseolin expression in tobacco chloroplast reveals an autoregulatory mechanism in heterologous protein translation. Issue 2 (1st June 2015) - De Marchis, Francesca; Bellucci, Michele; Pompa, Andrea
Summary: Plastid DNA engineering is a well‐established research area of plant biotechnology, and plastid transgenes often give high expression levels. However, it is still almost impossible to predict the accumulation rate of heterologous protein in transplastomic plants, and there are many cases of unsuccessful transgene expression. Chloroplasts regulate their proteome at the post‐transcriptional level, mainly through translation control. One of the mechanisms to modulate the translation has been described in plant chloroplasts for the chloroplast‐encoded subunits of multiprotein complexes, and the autoregulation of the translation initiation of these subunits depends on the availability of their assembly partners [control by epistasy of synthesis (CES)]. In Chlamydomonas reinhardtii, autoregulation of endogenous proteins recruited in the assembly of functional complexes has also been reported. In this study, we revealed a self‐regulation mechanism triggered by the accumulation of a soluble recombinant protein, phaseolin, in the stroma of chloroplast‐transformed tobacco plants. Immunoblotting experiments showed that phaseolin could avoid this self‐regulation mechanism when targeted to the thylakoids in transplastomic plants. To inhibit the thylakoid‐targeted phaseolin translation as well, this protein was expressed in the presence of a nuclear version of the phaseolin gene with a transit peptide. Pulse–chase and polysome analysis revealed that phaseolin mRNA translation on plastid ribosomes was repressed due to the accumulation in the stroma of the same soluble polypeptide imported from the cytosol. We suggest that translation autoregulation in chloroplast is not limited to heteromeric protein subunits but also involves at least some of the foreign soluble recombinant proteins, leading to the inhibition of plastome‐encoded transgene expression in chloroplast.